2001
DOI: 10.1016/s0042-6989(01)00169-9
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the biometric and refractive changes in full-term infants during the first year of life

Abstract: Changes in ocular axial dimensions and refraction were followed longitudinally, using ultrasonography and retinoscopy, during the first year of life (mean ages 4-53 weeks) of a group of 20 full-term infants (10 male, 10 female). Using a mixed-model regression analysis, axial length changes as a function of time were found to be best described by a quadratic expression (AL=17.190+0.128x-0.0013x(2), where AL is the axial length in mm and x is the age in weeks), while anterior chamber depth changed linearly (ACD=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 50 publications
7
95
1
Order By: Relevance
“…[9][10][11][12] Recent reports of data from Tohono O'odham infants show a high prevalence of astigmatism, which decreases in the second year of life. 12,13 This pattern is similar to that seen in Caucasian, Asian, and Hispanic infants: astigmatism is prevalent in infancy, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] but longitudinal studies indicate that the amount of astigmatism decreases significantly after the first year of life. 17,18,21,23,[28][29][30][31] However, cross-sectional data has shown that the initial decrease in prevalence of astigmatism after infancy in Tohono O'odham children is followed by an increase in prevalence by age 2 years to the level we see in Tohono O'odham preschool and school-age children.…”
Section: Introductionsupporting
confidence: 58%
“…[9][10][11][12] Recent reports of data from Tohono O'odham infants show a high prevalence of astigmatism, which decreases in the second year of life. 12,13 This pattern is similar to that seen in Caucasian, Asian, and Hispanic infants: astigmatism is prevalent in infancy, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] but longitudinal studies indicate that the amount of astigmatism decreases significantly after the first year of life. 17,18,21,23,[28][29][30][31] However, cross-sectional data has shown that the initial decrease in prevalence of astigmatism after infancy in Tohono O'odham children is followed by an increase in prevalence by age 2 years to the level we see in Tohono O'odham preschool and school-age children.…”
Section: Introductionsupporting
confidence: 58%
“…In children, lens power decreases with age; lens power decreases remarkably in infants who are one to two years old [24]. In growing children, lens power decreases due to the development of myopia [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…AL measurements and baseline VA evaluations were conducted before surgery ( Figure 1a) [22,26]. The dense and total cataracts hindered their preoperative RT measurement; consequently, the first RT measurement was conducted immediately following the cataract removal during the surgery (Figure 1b).…”
Section: Longitudinal Assessment Protocolmentioning
confidence: 99%
“…To determine the normal rate of AL development, the referenced curve-fitting value of the age-matched normal distribution range was used for comparison ( [22,26]. As shown in Figure 5, the presurgery AL of our population was distributed mainly in the normal curve range.…”
Section: Al Developmentmentioning
confidence: 99%
See 1 more Smart Citation